The Effect of Social Media on Gen Z, Impulse Buying and Lifestyle in Purchase Decisions - Yasin, Hanifa; Julita, Julita; Hidayat, Rahmat (AIBPM Publisher, 2023)
Social media provides wide and easy access to various brands, products, and user reviews. Generation Z can easily search for information about the products they are interested in, read reviews, and see recommendations from other users. This enables them to make more informed purchase decisions, but it can also lead to hasty decision-making. The purpose of this study is to examine the effects of social media on Gen Z, impulse buying, and lifestyle on fashion product purchase decisions in Medan City. This research adopts a quantitative approach. The population consists of Generation Z individuals in Medan City, with a purposive sample of 100 respondents. The research findings indicate that social media, impulse buying, and lifestyle have both partial and simultaneous effects on purchase decisions.